Effects of Alginate Based Coatings with Pomegranate Peel Extract on the Microbial Quality of Mackerel Fillets - Fatma Öztürk; Hatice Gündüz; Göknur Sürengil (Journal of Agricultural Sciences)
In this study, antibacterial effects of the pomegranate peel extract against food pathogens were investigated. Different concentrations of pomegranate peel extract (2.5, 5, 7.5 and 10%), which showed the highest antibacterial effect in vitro experiments were added to the alginate film. Mackerel fillets coated with the film solution prepared in this way were stored at 4±1 oC for 13 days. L. monocytogenes, total aerobic mesophilic bacteria, total aerobic psychrophilic bacteria, total yeast-mould and enterobacteriaceae counts were determined on 0, 3rd, 8th, and 13th day of storage period. At the end of the study; it was determined that the pomegranate extract was effective and the inhibition effect was also increased based on the increase in extract concentration. Different concentrations of pomegranate peel extract showed antibacterial effect against L. monocytogenes, E. coli O157:H7, and S. aureus (P<0.05). As a result of 13 days storage of mackerel fillets coated with alginate enriched with 2.5, 5, 7.5 and 10% PPE at 4 oC, the number of L. monocytogenes significantly decreased (P<0.05). During the storage period total aerobic mesophilic bacteria and enterobacteriaceae number were found to be significantly lower in the experimental groups used pomegranate peel extract in comparison with the control group. As a result, it was determined that pomegranate peel extract has a potential to be used as a natural preservative in seafood products.